The Β-Change by Finsler Metric of C-Reducible Finsler Spaces in Finsler Geometry - Mandal, Khageswar (Tribhuvan University Journal, 2019)
This paper considered about the β-Change of Finsler metric L given by L*= f(L, β), where f is any positively homogeneous function of degree one in L and β and obtained the β-Change by Finsler metric of C-reducible Finsler spaces. Also further obtained the condition that a C-reducible Finsler space is transformed to a C-reducible Finsler space by a β-change of Finsler metric.